Peter Lombard on God’s Knowledge: Sententiae, Book I, Distinctions 35-38, as the Basis for Later Theological Discussions - Tkachenko, Rostislav (Sententiae, 2017)
Since the mid-90’s the figure of Peter Lombard and his Book of Sentences has regained the importance in scholarly world and been studied from both historical-theological and historical-philosophical perspectives. But some aspects of his thinking, encapsulated in the written form, which was to become the material basis for the thirteenth- through the fifteenth-century theological projects, remained somewhat insufficiently researched. Therefore this article analyzes the select parts of the Book of Sentences with the purpose of looking at how Peter Lombard handled the issue of God’s knowledge. The article shows that for Peter Lombard God’s knowledge is God’s awareness of everything knowable. It has no causal power which belongs to the divine will. Nevertheless, this knowledge is able to function in two different modes: it can be either a purely cognitive act as awareness alone, or a double cognitive and voluntary act as awareness and simultaneous volition in the form of approbation. Hence, God’s knowledge in general is not causative, but God’s knowledge of the good must be causative because he simultaneously knows and wills what is good. The article reasonably suggests that Lombard’s logic implies the compatibility of God’s (fore)knowledge and voluntary activity, on the one hand, and the contingency of the created order and the rational creatures’ free will, on the other hand. But the details of this conception remain unrevealed as Lombard’s presentation of the problem is to be declared underdeveloped.